Effectiveness of Video and Lecture Methods on Basic Life Support Knowledge and Skills among Students of Poltekkes Kemenkes Surabaya: A Quasi-Experimental Study - Titani Anggarnis; Sari Luthfiyah; Nikmatul Fadilah; Endah Suprihatin (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Variations in Basic Life Support (BLS) knowledge and practical competence among students at Poltekkes Kemenkes Surabaya may influence their readiness to respond effectively in emergency situations. Differences in educational background and departmental focus contribute to disparities in students’ understanding and performance of BLS procedures, highlighting the importance of implementing appropriate educational strategies. This study aimed to evaluate and compare the effectiveness of lecture-based learning and educational video methods in improving BLS knowledge and practical skills among students. This study employed a quantitative quasi-experimental approach using a two-group pretest–posttest design. A total of 28 members of the Scout Student Activity Unit were selected through simple random sampling and randomly assigned into two intervention groups: lecture-based education and educational video-based learning. Data were collected using validated knowledge questionnaires and skill observation checklists administered before and after the interventions. Statistical analysis was conducted using the Wilcoxon Signed Rank Test to assess within-group differences and the Mann–Whitney U Test to compare outcomes between groups, with a significance level of p < 0.05. The findings demonstrated a statistically significant improvement in both BLS knowledge and practical skills following the interventions in each group (p = 0.001). However, no significant differences were identified between the lecture and educational video methods in improving knowledge (p = 0.378) or practical skills (p = 0.617), indicating that both approaches were equally effective. Lecture-based learning appeared to enhance conceptual understanding, whereas educational videos provided greater support for procedural and skill-based learning. In conclusion, both lecture and educational video methods are effective educational strategies for improving BLS knowledge and skills among students. The integration of these complementary approaches may optimize learning outcomes and strengthen students’ preparedness in emergency response situations.